Effect of Timing of Artificial Insemination on Fertility and Hatchability of Shikabrown Breeder Hens - Obidi, J.A.; Onyeanusi, B.I.; Ayo, J.O.; Rekwot, P.I.; Abdullahi, S.J. (International Journal of Poultry Science, 2008)
The influence of timing of artificial insemination on fertility and hatchability of breeder hens was carried out by inseminating breeder hens at 10:00 hr and 15:00 hr with pooled semen from Shikabrown White breeder cocks for four weeks. Fertile eggs were collected two days after the first insemination and stored at a temperature of 16oC for seven days before incubation. Fertility was higher (P < 0.05) in hens inseminated at 10:00 hr when sperm quality was optimal. The fertility values of 82.1 ± 1.0% and 85.0 ± 2.3% obtained in Shikabrown White and Shikabrown Red hens, respectively, for 10:00 hr insemination were significantly (P < 0.01) different from the corresponding values of 76.0 ± 3.2% and 78.3 ± 2.5% recorded at 15:00 hr insemination in the Shikabrown White and Shikabrown Red hens, respectively. The hatchability values of 72.5 ± 2.8% and 67.0 ± 3.3% were obtained for Shikabrown White and Shikabrown Red hens, respectively, for the morning hour insemination. These values were significantly (P < 0.01) different from the corresponding values of 65.0 ± 1.0% and 63.0 ± 1.1% obtained in the Shikabrown White and Shikabrown Red hens, respectively, for 15:00 hr insemination. The results showed that timing of artificial insemination influence fertility in Shikabrown breeder hens and this is probably mediated by meteorological factors. In conclusion for better fertility of Shikabrown hens, insemination should be carried out at 10:00 hr.